O estado populista como alternativa social da modernidade brasileira no contexto latino-americano - Bolzan, Moacir (2006)
The execution of the modernity project proposed by the capitalist system depends fundamentally of the moment and place where it happens. That allows us to affirm that in Latin America and, particularly in Brazil, it assumes late outlines and it executes historically the deep marks of the slavery and, therefore, of the exclusion. This affects vastly its socio-cultural dimension that establishes a dispute among the pillars of the regulation and of the emancipation that are constituted in its support. In this game, the pillar of the regulation generates a system of social protection that it tends to consecrate rights noticed as privileges/benefits by the citizen, in the pillar of the emancipation, once the State associated to the Community s principle. This articulation alters the sense of Citizenship in Brazil and the order established by the liberal version in the construction of the rights. Here, the social ones preceded the civil and the political ones. This practice which prioritized the regulation to the detriment of the emancipation and it advanced social rights, especially the ones linked to the work, including social segments, until then to the margin of the productive process, in the periphery of the capitalist system, in the period of 1930/45, fell to the Populist State. With no doubt, it was constituted in a social alternative for the modernity in Latin America.